Deciding How to Decide - Courtney, Hugh; Lovallo, Dan; Clarke, Carmina (Harvard business review)
Most businesses rely on traditional capital-budgeting tools when making strategic decisions such as investing in an innovative technology or entering a new market. These tools assume that decision makers have access to remarkably complete and reliable information - yet most strategic decisions must be made under conditions of great uncertainty. Why are these traditional tools used so often even though their limitations are widely acknowledged? The problem is not a lack of alternatives. Managers have at their disposal a wide variety of tools - including decision analysis, scenario planning and information aggregation tools - that can help them make smart decisions under high degrees of uncertainty. But the sheer variety can be overwhelming. This article provides a model for matching the decision-making tool to the decision being made, on the basis of three factors: 1. how well you understand the variables that will determine success; 2. how well you can predict the range of possible outcomes; and 3. how centralized the relevant information is. The authors bring their framework to life using decisions that executives at McDonald's might need to make - from the very clearcut (choosing a site for a new store in the US) to the highly uncertain (changing the business in response to the obesity epidemic).